Plant-Vector-Pathogen Interactions in the Context of Drought Stress - Szczepaniec, Adrianna; Finke, Deborah (Frontiers in Ecology and Evolution, 2019)
Plants regularly encounter stress, and their responses to abiotic and biotic stressors have been a focus of research for decades. Stress caused by drought is one of the most often studied abiotic stresses owing to the increase in the incidence of drought driven by climate change. Severe drought has been shown to elicit a whole-plant response guided by key phytohormones, which not only respond to water stress but also play a critical role in the response of plants to biotic stress imposed by herbivores and pathogens. This is especially relevant for insect-transmitted pathogen systems, where plants, herbivores, and pathogens are linked in a web of direct and indirect interactions. Few studies have thus far explored the complex nature of drought-mediated tripartite interactions, however, and our ability to generalize and predict how plants respond to herbivore-transmitted pathogens while simultaneously countering the consequences of drought remains limited. The goal of this mini-review is to assess the current state of the field regarding the molecular mechanisms underlying plant responses to the combined effects of drought and simultaneous herbivory and pathogen transmission and their ecological consequences. We discuss plant responses to drought, herbivory, and pathogens as distinct and concurrent stresses, and highlight the implications of the tripartite interactions on insect vector and pathogen suppression in agroecosystems. This review provides a framework for future research linking generalized molecular responses in drought-stressed plants to tripartite species interactions and the ecology of insect-transmitted pathogens in the context of modern agriculture and water deficit driven by climate change.